Produtividade da soja e severidade de ferrugem asiática (Phakopsora pachyrhizi) influenciadas pela aplicação foliar com fontes de potássio e doses de Tebuconazole - Oliveira, Angelo Fernandes de (2007)
Of macronutrients cited in scientific literature, the potassium is the element that presents consistent positive results in the reduction the incidence of pests and diseases. Reports show that nutrition potassica adequately reduced the severity of more than 20 diseases bacterial, more than 100 diseases fungal and of 10 diseases caused by viruses and nematoides in diverse cultures. Thus, this study evaluated leaf sprays of potassium sources associated with different doses of the fungicide Tebuconazole (200g a.i. l-1), its effect on soybean Asian rust (Phakopsora pachyrhizi) severity and progress and on grain yield. The experimental design was randomized blocks, in a 5 x 4 factorial scheme, using four potassium sources (Nitrate, Sulfate, Phosphite, Silicate), and a nonsprayed control, and four fungicide doses (0, 250, 500, 750 ml ha-1), in a total of 20 treatments. The doses of each fertilizer was determined based on the application of 200 g ha-1 potassium on the first and second sprays, and 400 g ha-1 potassium on the third spray, in a total of 800 g ha-1 potassium. Previously inoculated soybean (M-Soy 8001) was sown on December 05 2006. The following yield components were evaluated: yield, weight of 1,000 grains, agronomic efficacy of the K sources, and efficacy on supplying K, rust severity and area under the disease progress curve (AUDPC). The spraying of different potassium sources did not affect soybean yield significantly; potassium silicate was the source with greatest agronomic efficacy and greatest efficacy on potassium supply; rust severity, evaluated on soybean stage R5.4, was slightly reduced on the lower third in the treatments with potassium sources, regardless of the association with the fungicide.